Pemanfaatan Layanan Whatsapp Gateway sebagai Sistem Notifikasi Pinjaman (SINOPI) di Dinas Kearsipan dan Perpustakaan Kota Pekalongan - Yuyun Siti Khoeriyah; Rosiana Nurwa Indah; Farah Ruqayah (Institut Agama Islam Negeri Salatiga, 2021)
This study aims to determine the use of the whatsapp gateway service in the loan notification system (SINOPI) at the Pekalongan City Library and Archives Service. The method used in this research is a qualitative method with descriptive analysis. The data collection technique used in this research is by conducting interviews. The informants in the study used purposive sampling technique, namely the technique of determining informants based on certain criteria. This study resulted in the finding that this service could at least minimize the delay in returning books by as much as 20 copies per day. This service has been used by all users who have registered as members of the Pekalongan City Regional Library. With this system, the service for extending the loan period is automatically served by the server without having any officers on guard and without having to come to the library location. This application development is easy to use and understand by its users and easy to access. The obstacles that often occur are notification information that is not conveyed or cannot be read by users due to several factors including; a power cut by PLN so that the server is down and unable to send notifications, the registered user cellphone number is no longer active / changed the number, because the internet subscription (kouta) of the user has run out and notifications are ignored.